Effect of Jasonia glutinosa on immune and oxidative status of gilthead seabream (Sparus aurata L.). Issue 100 (May 2020) - Espinosa, Cristóbal; García Beltrán, José María; Messina, Concetta Maria; Esteban, María Ángeles
Abstract: Jasonia glutinosa (rock-tea, RT) has numerous biological activities . In the present work, the beneficial effects of dietary RT on gilthead seabream ( Sparus aurata L.) were studied. Fish fed experimental diets containing 0 (control), 10 or 30% of RT for 15 and 30 days. Samples from skin mucus, blood, head kidney, liver and gut were obtained at 15 and 30 days. The antioxidant properties from RT were analysed such as the antioxidant capacity and phenolic content. The heat shock protein 70 level (HSP70) and the total oxidized proteins were evaluated on skin mucus as stress markers. Immune parameters, both humoral (peroxidase activity, immunoglobulin M levels and complement activity) and cellular (phagocytic, respiratory burst and peroxidase activities) were determined in skin mucus, serum or head-kidney leucocytes, respectively. Concomitantly, the expression of different genes related to inflammation and oxidative stress was studied both in liver and gut. Skin mucus peroxidase was significantly increased on fish fed 10% RT for 15 days with respect to the control group. In addition, Serum IgM levels were significantly increased while HSP70 levels and oxidized proteins were significantly decreased on skin mucus from fish fed 30% RT for 30 days, respectively. Besides, cellular immune parameters (phagocytosis, respiratory burst and peroxidase activity) were significantly higher in leucocytes from fish fed the RT diets for 15 days, but not for 30 days. Finally, the gene expression of antioxidant enzymes was up-regulated in liver at 15 and in liver and gut at 30 days. However, the expression of il1b and hsp70 was down-regulated in the liver of fish fed 30% RT for 30 days with respect to the values of control fish. The possible inclusion of RT in fish diets as an additive with antioxidant and/or immunostimulant activities is discussed. Highlights: The beneficial effects of Jasonia glutinosa (RT) on gilthead seabream were studied. The immunostimulant effects of dietary RT are evident after 15 days of treatment but not after 30 days. The antioxidant protection is evident at 15 and 30 days of RT dietary administration. The possible inclusion of RT in fish diets as an additive with antioxidant and/or immunostimulant activities is discussed.